The impact of total caloric and macronutrient consumption on strength and power during an off-season training program in collegiate volleyball players - Figueroa, Y.; Perry, A. (International Journal of Strength and Conditioning, 2023)
Adequate caloric and carbohydrate intakes are necessary for positive adaptations to exercise training, yet there is limited research examining dietary intake in relation to strength and power in female athletes. The purpose of this study was to determine 1) whether there were significant changes in weekly total caloric and macronutrient consumption, strength, and power, and 2) whether total caloric and macronutrient consumption significantly and positively contributed to changes in strength and power across a controlled eight-week, off-season resistance training program. Eleven collegiate-level female volleyball players were examined on macronutrient consumption, strength, and power at two-week intervals using three-day food logs, 3-repetition maximum bench press and back squat, and vertical jump, respectively. Five assessments were conducted on each subject. Alpha level was set at r < 0.05. Paired samples t-tests showed improvements in body mass index, lean body mass, percent body fat, and lower body strength and power following eight weeks of training (r < .05) despite no significant changes in total calories or macronutrients. Results of a weighted regression analysis indicated that both total caloric consumption and carbohydrate intake influenced lower body power after training (r < .05). However, nutrient intake did not impact strength or power at any of the two-week intervals. We believe these findings are related to the neuromuscular adaptations that occur early in training. A longer resistance training program resulting in gains in muscle cross-sectional area (CSA) may be necessary to further examine the contribution of calories and macronutrients to performance-related variables.